2017
DOI: 10.1155/2017/2467940
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of ROS in Cancer Heterogeneity and Therapy

Abstract: Cancer comprises a group of heterogeneous diseases encompassing high rates of morbidity and mortality. Heterogeneity, which is a hallmark of cancer, is one of the main factors related to resistance to chemotherapeutic agents leading to poor prognosis. Heterogeneity is profoundly affected by increasing levels of ROS. Under low concentrations, ROS may function as signaling molecules favoring tumorigenesis and heterogeneity, while under high ROS concentrations, these species may work as cancer modulators due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(137 citation statements)
references
References 113 publications
1
135
0
1
Order By: Relevance
“…It has been reported that ROS participate in various pathways and can control cellular stability . ROS may function as vital signaling molecules, which can favor tumorigenesis . For example, restraining ROS in Listeria monocytogenes can promote glial cells apoptosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that ROS participate in various pathways and can control cellular stability . ROS may function as vital signaling molecules, which can favor tumorigenesis . For example, restraining ROS in Listeria monocytogenes can promote glial cells apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…21 ROS may function as vital signaling molecules, which can favor tumorigenesis. [22][23][24] For example, restraining ROS in Listeria monocytogenes can promote glial cells apoptosis. 25 ROS-responsive miR-210 can modulate adipose-derived stem cells proliferation and migration via targeting PTPN2.…”
Section: Discussionmentioning
confidence: 99%
“…Rola RFT w komórkach nowotworowych zależy od ich ilości. Niewielkie ilości RFT działają jako cząsteczki sygnałowe, indukując kancerogenezę oraz heterogeniczność, natomiast w dużych ilościach mogą działać jako modulatory nowotworu, wykazując genotoksyczny lub nawet proapoptotyczny efekt w komórkach nowotworowych [17].…”
Section: Wprowadzenieunclassified
“…The Tin (II) chloride complexes with many Schiff base derivative of 2-Hydroxy-1-naphthaldehyde (HN) have been synthesized and screened for their antioxidant activities by DPPH technique. All the complexes showed great antioxidant activities and better antioxidant activities than their corresponding ligands [86][87][88]. Schiff bases of Sulphanilamide and its complexes with elements like Cu, Zn and Cd metals have been tested as an antioxidant.…”
Section: Antioxidant Activitymentioning
confidence: 99%